Quantitative Analysis of Microbial Burden on Hospital Room Environmental Surfaces Contributing to Healthcare-Associated Infections. (4th October 2017) - Rutala, William A; Kanamori, Hajime; Gergen, Maria; Sickbert-Bennett, Emily; Knelson, Lauren P; Chen, Luke F; Anderson, Deverick; Sexton, Daniel; Weber, David J
Abstract: Background: Contaminated environmental surfaces are involved in the transmission of epidemiologically important pathogens. It remains unknown which level of microbial load can contribute to healthcare-associated infections (HAI). We used microbiological data obtained from the Benefits of Enhanced Terminal Room (BETR) Disinfection Study to investigate the quantitative relationship between microbial burden and risk of HAI. Methods: Microbiological samples were collected from high-frequency-touch hospital room surfaces using Rodac plates (25 cm 2 /plate) in rooms after terminal room disinfection. All rooms were randomly assigned to standard disinfection (Quaternary ammonium [Quat]) or an enhanced disinfection (Quat/ultraviolet light [UV-C], Bleach, Bleach/UV-C). The Quat/UV-C arm was excluded from further analysis since HAI were not observed in this arm. All new patients in study rooms were monitored for HAI following terminal disinfection through the BETR study standard protocols. We analyzed the relationship between the total colony forming units (CFU) of bacterial loads from 2, 395 environmental samples in 60 rooms and HAI among new patients in the room (6 patients with HAI and 54 patients without HAI). Each arm had 2 patients with HAI. Statistical significance was determined by the Wilcoxon test, and P < 0.05 was considered significant. Results: Overall, samples in rooms of patients with HAI had a mean 39.3 CFU, while samples from rooms of patients without HAI had a mean 35.6 CFU (Table 1). In the standard disinfection, the sampled rooms from the HAI patients had a significantly higher number of total CFU (mean 65.1 CFU) than non-HAI group (mean 35.5 CFU) ( P = 0.019). In the enhanced disinfection rooms, there was no statistical significance between HAI and non-HAI groups. Conclusion: Although our sample size may have been too small to detect contaminated microbial load in a room though a large clinical trial was conducted, our data based on the Quat arm as standard disinfection demonstrated the significant relationship between microbial load and HAI. Disclosures: D. Sexton, Centers for Disease Control and Prevention: Grant Investigator, Grant recipient. Centers for Disease Control and Prevention Foundation: Grant Investigator, Grant recipient. UpToDate: Collaborator, Royalty Recipient. D. J. Weber, PDI: Consultant, Consulting fee